2018
DOI: 10.1101/298570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hippocampal knockdown of Piwil1 and Piwil2 enhances contextual fear memory in mice

Abstract: The Piwi pathway is a conserved gene regulatory mechanism comprised of Piwi-like proteins and Piwiinteracting RNAs, which modulates gene expression via RNA interference and epigenetic mechanisms.The mammalian Piwi pathway has been defined by its role in transposon control during spermatogenesis, and despite an increasing number of studies demonstrating its expression in the nervous system, relatively little is known about its function in neurons or potential contribution to gene regulation in the brain. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Earlier work from our laboratory detected low-level expression of Piwil1 and Piwil2 in cultured mouse neurons; both genes are dynamically upregulated by neuronal stimulation, and they promote activity-dependent chromatin relaxation at the Ppp3r1 locus which is required for binding of the regulatory factor ING1 and subsequent expression of Ppp3r1 [ 97 ]. We have also detected expression of all three mouse Piwi-like genes in the adult hippocampus, and have shown that simultaneous knockdown of Piwil1 and Piwil2 in the hippocampus enhances contextual fear memory without affecting generalised anxiety [ 98 ].…”
Section: Small Rnasmentioning
confidence: 99%
“…Earlier work from our laboratory detected low-level expression of Piwil1 and Piwil2 in cultured mouse neurons; both genes are dynamically upregulated by neuronal stimulation, and they promote activity-dependent chromatin relaxation at the Ppp3r1 locus which is required for binding of the regulatory factor ING1 and subsequent expression of Ppp3r1 [ 97 ]. We have also detected expression of all three mouse Piwi-like genes in the adult hippocampus, and have shown that simultaneous knockdown of Piwil1 and Piwil2 in the hippocampus enhances contextual fear memory without affecting generalised anxiety [ 98 ].…”
Section: Small Rnasmentioning
confidence: 99%
“…Among these 103 piRNAs expressed differentially. piRNAs could be considered as potential biomarkers for Alzheimer disease diagnosis ( 66 ). piRNAs may act as novel gene expression regulators and stimulate metabolic phenotypes.…”
Section: Introductionmentioning
confidence: 99%